The Impact of Globalization on Regional Development Urban and Rural Sustainable Development in Indonesia - Khairunissa Yulianto, Arrizqy Nadya; Hidayaturahmi, Amy; Triyulianto, Toni (Westscience Press, 2025)
This study is aimed to examine how sustainable regional development in urban and rural areas is affected by globalization and what strategy can be implemented to address these condition. The economic development orientation that emphasizes growth has also exacerbated regional disparities, especially between rural and urban areas. The theory of urban planning development and rural planning development becomes the focus of this study. This study employs a comprehensive literature review approach to explore and synthesize the prevailing theories of rural planning and sustainable development. The study found that the imbalance between urban and rural development, which is inseparable from the influence of globalization. The model of sustainable development is expected to address the challenges that arise. It is necessary to linkage rural and urban areas through the provision of food and other materials for consumption and production, to strengthen local economic management, and to enhance the capacity of rural community economic institutions and organizations.